Socio-Cultural Influence on Buffalo Prices in Toraja Society (Agrikan Jurnal Agribisnis Perikanan, 2022)
In Toraja, buffaloes cannot be separated from the socio-cultural life of the Toraja people. Culture is something that cannot be separated from human life. Communities interact with each other, create and develop a culture within the cultural system. This research was conducted with the aim of knowing how socio-cultural influences the price of buffalo in the Toraja people. It will be held from July to August 2021. The informants consist of 5 people. Research data consists of primary and secondary data. The results of the study show that, in the socio-cultural life of the Toraja people, it influences the price of buffalo. Owned culture such as the Rambu Solo Ceremony has a major influence on buffalo prices. Where the existence of this traditional ceremony makes the price of existing buffalo expensive. As for buying buffalo, the Toraja people also have a perception of buffalo which also makes the price of buffalo more expensive which can be seen from the characteristics of the buffalo.
Keywords: Buffalo; Social, Cultural; Toraja